Role of Cannabinoid Receptor Type 1 in Insulin Resistance and Its Biological Implications - Nagappan, Arulkumar (Int J Mol Sci, 2019)
Endogenous cannabinoids (ECs) are lipid-signaling molecules that specifically bind to cannabinoid receptor types 1 and 2 (CB1R and CB2R) and are highly expressed in central and many peripheral tissues under pathological conditions. Activation of hepatic CB1R is associated with obesity, insulin resistance, and impaired metabolic function, owing to increased energy intake and storage, impaired glucose and lipid metabolism, and enhanced oxidative stress and inflammatory responses. Additionally, blocking peripheral CB1R improves insulin sensitivity and glucose metabolism and also reduces hepatic steatosis and body weight in obese mice. Thus, targeting EC receptors, especially CB1R, may provide a potential therapeutic strategy against obesity and insulin resistance. There are many CB1R antagonists, including inverse agonists and natural compounds that target CB1R and can reduce body weight, adiposity, and hepatic steatosis, and those that improve insulin sensitivity and reverse leptin resistance. Recently, the use of CB1R antagonists was suspended due to adverse central effects, and this caused a major setback in the development of CB1R antagonists. Recent studies, however, have focused on development of antagonists lacking adverse effects. In this review, we detail the important role of CB1R in hepatic insulin resistance and the possible underlying mechanisms, and the therapeutic potential of CB1R targeting is also discussed.